Atividade formicida de Aristolochia trilobata L. (Aristolochiaceae) sobre formigas cortadeiras - Oliveira, Bruna Maria Santos de (2015)
Leaf-cutting ants of Atta and Acromyrmex genus (Hymenoptera: Formicidae) are common insects in the Neotropics region and an important pests in agricultural environments. These organisms are often controlled using organosintetics insecticides, however, mostly products are inefficient. This problem has generated a growing demand for environmentally safe products to control these pests. Thus, in order to contribute with new methods of control, the aim of this work was to evaluate the ant activity of essential oil of A. trilobata and its major compounds on cutting ants Atta sexdens and Acromyrmex balzani. Initially, it was performed toxicity bioassays by two different routes of exposure - contact and fumigation. Once determined the exposure way with the best ant activity, this route was choosed to performe the next experiments, bioassay toxicity (lethal concentration and time), effects of binary mixtures (synergistic, additive and antagonistic) of major compounds, repellency and irritability. The essential oil of A. trilobata was obtained by hydrodistillation of the dried stem and the identification / quantification of compounds was performed by GC/MS/FID. Twenty Five compounds were identified in the essential oil of A. trilobata, that are mostly composed of monoterpenes. The major constituents were the monoterpenes: sulcatyl acetate (25.64%), limonene (24.80%), p-cymene (10.41%) and linalool (9.51%). The essential oil of A. trilobata and their major compounds were effective against workers of A. balzani and A. sexdens when the route of exposure was fumigation. These compounds have demonstrated efficient activity on ant species A. balzani and A. sexdens, with LCs50 ranging from 2.18 to 6.73 uL mL-1. The monoterpenes linalool and sulcatyl acetate when applied alone were 1.6 and 1.7 times more toxic than the essential oil against A. balzani. As for A. sexdens, p-cymene was 1.6 times more toxic than the essential oil of A. trilobata. Workers of A. sexdens were more tolerant to the essential oil, linalool and sulcatyl acetate. The essential oil of A. trilobata and its major compounds acted faster on A. sexdens compared to A. balzani. On average, these compounds took 29.3 and 11.3 hours to cause mortality in half population of A. balzani and A. sexdens, respectively. The major compounds of the essential oil of A. trilobata acted synergistically in toxicity of A. balzani. As for A. sexdens most combinations of the compounds exhibited an additive effect. The essential oil of A. trilobata and its major compounds were repellent and caused great irritability to workers of A. balzani and A. sexdens. Thus, our results show a great potential of the essential oil of A. trilobata and its major compounds for develop new insecticides.